Does the implementation of a closed fishing season during the breeding season benefit a species? : a per-recruit-based approach using Cymbula granatina as an illustration - Govender, Anesh ;Arendse, Clement (Department of Biological Sciences, 2017)
Closed seasons are generally implemented on the presumption that they increase reproductive output of fished populations. This is based on the assumption that the imposition of a closed season during the breeding season allows more individuals to reproduce, as they are not being harvested. I evaluated the validity of imposing closed seasons during the breeding season by creating a simulation model using the limpet Cymbula granatina as a test case and then compared the fol lowing four scenarios: 1) an unharvested population; 2) no closed season imposed; 3) a closed season imposed during the breeding season; and 4) a closed season imposed outside the breeding season, to determine the effects of the latter three situations on the reproductive output and yield. It was determined that closed seasons do not significantly affect the reproductive output of the population and that the timing of closed seasons made no difference to the reproductive output of the population, as the output was the same for populations with closed seasons during the breeding season or outside the breeding season. Survivors, catch in numbers and yield in biomass were affected by the timing of closed seasons, with higher outputs for each obtained when the closed season was closer to the month when individuals become of harvestable size. It was thus concluded that the imposition of a closed season at any time of the year is an effective management measure if imposing the closed season can reduce annual fishing mortality, but the imposition of a closed season specifically during the breeding season with a view to increase reproductive output brings no benefits relative to closure at any other time of the year. Moreover, any closure will be ineffective if it does not also bring about a reduction of annual fishing mortality. The reasons for advocating closure of a fishery during the breeding season are thus based on false grounds in the case of the limpet C. granatina.